Comparative Analysis of Profits of Organic and Non-organic Fluted Pumpkin Production in Rivers State, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study examines the profits of organic and non-organic farming among small holder fluted pumpkin farmers in Rivers State. A multistage sampling technique was employed in the selection of location and respondents. The data were collected from 240 organic and non-organic small holder fluted pumpkin farmers. The primary instrument used for data collected was structured questionnaire. Data obtained was analyzed with Enterprise budgeting method and Analysis of Variance (ANOVA). Results indicated that the average profit realized by organic fluted pumpkin farmers in Rivers State was N 280,570, while the average profit realized by non-organic was N101, 050. The result of Analysis of Variance reveals that there is a statistically significant difference in the mean profit of organic fluted pumpkin production and non- organic (conventional system) of fluted pumpkin production in the study area at 1% probability level. The result indicates that the difference between the mean profit in organic farming technology and non-organic farming technology was not statistically different at 1% probability level. The mean profit in subset two which comprises organic and non-organic technology was also not statistically significant at 1% probability level. The study suggested that extension agents should train farmers frequently for easy adoption of the technology.